MICROTEXTURAL CONTROLS OF WEATHERING OF PERTHITIC ALKALI FELDSPARS - Lee M.R.; Parsons I. (My University, 1995)
The relationship between the microtexture and dissolution behaviour of fresh, HF acid-etched and naturally weathered alkali feldspar phenocrysts from the Lower Devonian Shap granite has been investigated by SEM and TEM. A novel resin impregnation technique has revealed the three dimensional shape and interconnectivity of etch pits beneath the weathered crystal surface. Further electron microscope work suggests that Shap phenocrysts are representative of the alkali feldspar in the protolith of many soils.Fresh and unweathered Shap feldspars have a complex microtexture, comprising areas of pristine cryptoperthite and lamellar microperthite cross-cut by volumes of microporous altered feldspar of ''patch perthites.'' Cryptoperthites are made up of <75 nm wide albite exsolution lamellae (platelets) in tweed orthoclase, whereas lamellar microperthites contain>75 nm wide albite films. The platelets are coherent, but albite films have numerous edge dislocations along their interface with orthoclase; (001) and (010) cleavage surfaces intersect #2-3 edge dislocations/μm2. In three dimensions, these edge dislocations form an orthogonal net in the ''Murchison plane'' of easy fracture, close to (601). Patch perthites are irregular, semicoherent to incoherent intergrowths of albite and irregular microcline subgrains, with #0.65-0.70 sub-μm to μm-sized pores/μm2. Microporous patch perthites form by dissolution-reprecipitation reactions with magmatic or hydrothermal fluids and pores are present before the alkali feldspars enter the weathering regime.Dissolution of Shap feldspars during natural weathering and laboratory acid etching is controlled by their microtexture, especially by dislocations and exsolution lamellae. The core and strain energy associated with dislocation outcrops on (001) and (010) cleavage surfaces promotes rapid dissolution at those sites and formation of nm-sized etch pits after <30 s of laboratory etching with HF acid vapour. With progressive HF etching, crystallographically controlled differences in the reactivity of etch pit walls cause them to expand more rapidly into orthoclase than albite. Naturally weathered feldspars were collected from the glacial erratic boulders, fine gravels surrounding exposed granite surfaces, and from peat soil overlying the granite. During natural weathering, etch pits on microperthites enlarge almost exclusively by dissolution of albite and resin casts demonstrate that they can penetrate =< 15 μm below the cleavage surface, forming an interconnecting, ladder-like grid of submicrometer wide channels in the Murchison plane. Coherent albite platelets and volumes of albite between dislocations in films dissolve uniformly, but faster than orthoclase. This is probably because the albite lamellae have significant elastic coherency strain, but this is much less, per unit volume of albite, than the core and strain energy associated with edge dislocations. Patch perthites etch in HF vapour and weather rapidly in nature to produce a honeycomb-like texture of interconnecting nanometer- to micrometer-sized pits, which nucleate at preexisting micropores or incoherent subgrain boundaries. The size and density of etch pits on microperthite surfaces, which is determined by rates of growth and coalescence, may be a useful progress variable for natural and experimental dissolution.All alkali feldspars are highly heterogeneous materials whose chemical composition and microtexture can vary on a submicrometer scale. These microtextures are critical variables with regard to the origin of surface roughness of fresh and weathered grains, the controls on absolute dissolution rates and why they commonly change over time, the nonlinear variation of dissolution rate with grain size, the ratio of alkali ions released into solution, and disparities between laboratory dissolution rates and those observed in the field.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская